2019
DOI: 10.3400/avd.oa.19-00085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Characteristics of IgG4-Related Periaortitis/Periarteritis and Retroperitoneal Fibrosis Diagnosed Based on Experts’ Diagnosis

Abstract: IgG4-related disease is a systemic disease, characterized by elevation of serum IgG4 and, histopathologically, massive infiltration of IgG4+ lymphocyte and plasma cell infiltration, storiform fibrosis, causing enlargement, nodules or thickening. It may affect various organs simultaneously or metachronously. Here we analyzed the clinical and pathological characteristics of 99 patients diagnosed with IgG4-related periaortitis/periarteritis and retroperitoneal fibrosis. Of 99 patients (women/men, 15/84; mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 28 publications
3
43
0
2
Order By: Relevance
“…Although ectopic GC frequently form in head and neck lesions [ 9 , 25 ], very few cases with IgG4-TIN accompanied by GC formation in kidney lesions have been reported [ 12 14 ]. Similarly, the frequency of ectopic GCs is rare and their number is small in the pancreas and retroperitoneal lesions [ 26 ]. TLT formation reflects the immune response against locally displayed antigens [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although ectopic GC frequently form in head and neck lesions [ 9 , 25 ], very few cases with IgG4-TIN accompanied by GC formation in kidney lesions have been reported [ 12 14 ]. Similarly, the frequency of ectopic GCs is rare and their number is small in the pancreas and retroperitoneal lesions [ 26 ]. TLT formation reflects the immune response against locally displayed antigens [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese multicenter study investigating 99 patients with IgG4-related periaortitis/periarteritis and retroperitoneal fibrosis showed the prevalence of kidney lesion to be 16.2%. 31 A Chinese retrospective study analyzing 58 patients with IgG4-related RPF among 407 with IgG4-RD reported 25.9% of cases with kidney lesion in the 58 patients. 9 On the other hand, non-IgG4-related IRPF rarely has extra-retroperitoneal lesions including renal ones.…”
Section: Prevalence Of Renal Involvement In Rpfmentioning
confidence: 99%
“…These lesions tend to be detected in men in their sixties. 11 Other differential diagnoses include infection (bacterial, syphilis, human immunodeficiency virus, and tuberculosis), drug-induced disease, 12 malignancy, 13 Behçet disease, Cogan syndrome, systemic lupus erythematosus, and anti-neutrophil cytoplasmic antibody-related vasculitis ( Supplementary material online, Figure S2 ). 14 The differential diagnosis needs to be performed based on the characteristics of the diseases in addition to the imaging evaluation.…”
Section: Discussionmentioning
confidence: 99%